Praying through kenosis - D. T. Williams (Acta Theologica)
From the very beginning, the practice of intercessory prayer has been an accepted part of Christian life, yet it has often been felt to be in conflict with the Christian view of God. Even though prayer has been understood as part of a relationship with God, ascribing omniscience to him has been felt to render intercession superfluous. However, understanding God as limiting himself in kenosis for the sake of relating to people, on the one hand, means that prayer is a reality as it really affects God, and changes the future, and, on the other hand, retains the traditional view of God as totally sovereign, which includes his omniscience. Then, if God’s approach to people is kenotic, the response of people to God, especially in prayer, should likewise be in the humility of kenosis.